2020
DOI: 10.34172/mejdd.2020.179
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Detection of Epstein–Barr Virus, Human Herpes Virus 6, Cytomegalovirus, and Hepatitis B Virus in Patients with Multiple Sclerosis

Abstract: BACKGROUND Multiple sclerosis (MS) is a chronic disease with significant morbidity. A wide spectrum of risk factors has been suggested that triggers the development of MS. Among them, several viral infections have been implicated to play a role in MS pathogenesis. We aimed to evaluate the relationship between viral diseases, including Epstein–Barr virus (EBV), human herpes virus 6 (HHV-6), cytomegalovirus (CMV), and hepatitis B virus (HBV) and MS in the present case-control study. METHODS About 100 patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…Indeed, the study revealed that EBV prevalence showed a higher frequency in HC than in MS patients, and that only a small percentage of MS patients had EBV DNA in peripheral blood (12.9%). Consistent with our observation, a recent Iranian study showed that EBV infection was more prevalent in non-MS subjects than in MS patients and no significant association was found between the occurrence of EBV infection and the development of MS[19]. Another Italian study used RT-PCR to examine the DNA of a group of HHVs (HSV-1 and -2, CMV, VZV and EBV) in the cerebrospinal fluid (CSF) and serum of MS patients and all samples were negative for HHV DNA except for one CSF sample among 56 MS patients, which was positive for EBV DNA[22].…”
supporting
confidence: 92%
See 1 more Smart Citation
“…Indeed, the study revealed that EBV prevalence showed a higher frequency in HC than in MS patients, and that only a small percentage of MS patients had EBV DNA in peripheral blood (12.9%). Consistent with our observation, a recent Iranian study showed that EBV infection was more prevalent in non-MS subjects than in MS patients and no significant association was found between the occurrence of EBV infection and the development of MS[19]. Another Italian study used RT-PCR to examine the DNA of a group of HHVs (HSV-1 and -2, CMV, VZV and EBV) in the cerebrospinal fluid (CSF) and serum of MS patients and all samples were negative for HHV DNA except for one CSF sample among 56 MS patients, which was positive for EBV DNA[22].…”
supporting
confidence: 92%
“…In the case of MS, EBV has been closely associated with disease risk as EBV seropositivity has been associated with increased susceptibility to MS, and the virus has been suggested to be involved in the pathogenesis of MS and may be considered a prerequisite for disease progression [11], [18]. However, most studies have targeted EBV in MS in terms of antiviral antibody detection, while molecular evaluation of EBV has shown inconsistent results in different ethnic groups [19]. Therefore, the current study was conducted to evaluate the relationship between MS and the incidence of EBV infection in Iraqi patients with RRMS using real time-polymerase chain reaction (RT-PCR) assay as a sensitive molecular method for detection of EBV DNA.…”
Section: Introductionmentioning
confidence: 99%
“…Different viruses have been shown to correlate with the pathology of brain diseases. Enterovirus and human herpesvirus are associated with ALS ( 176 , 177 ), while Epstein-Barr virus (EBV), cytomegalovirus, and varicella-zoster virus have been reported in MS patients ( 178 , 179 ). In addition, Japanese encephalitis virus (JPV) and influenza virus have been identified in patients with PD ( 180 ), while three strains of human HSV have been found in the brain samples of AD patients ( 181 – 183 ).…”
Section: Infective Neuroinflammation and Neurodegenerationmentioning
confidence: 99%
“…These studies have offered substantial epidemiological data proving that those suffering from MS exhibit a greater correlation than controls. 40 The aetiology of MS has been linked to various infectious agents, but no single pathogen has been identified as the cause. 41 The link between infections and MS is still a mystery because most infectious agents associated with MS over the years have not been confirmed in subsequent studies.…”
Section: Discussionmentioning
confidence: 99%
“…Several meta‐analyses have been conducted concerning the seroepidemiological linkages of SARS‐CoV‐2, EBV, CMV, and HHV‐6 with MS. These studies have offered substantial epidemiological data proving that those suffering from MS exhibit a greater correlation than controls 40 . The aetiology of MS has been linked to various infectious agents, but no single pathogen has been identified as the cause 41 .…”
Section: Discussionmentioning
confidence: 99%